PENGARUH KESIAPAN GURU TERHADAP PENINGKATAN KUALITAS PEMBELAJARAN PASCA IMPLEMENTASI KEBIJAKAN RPM DI SEKOLAH DASAR - Aura Setya Maharani; Ifa Unifah; Salma Nabilah Diaulia (Al-mujahidah, 2026)
This study was motivated by changes in learning policies through the implementation of the In-Depth Learning Plan (RPM), which requires teachers to be prepared. This study aims to describe teachers' readiness and analyze its effect on learning quality. The method used is qualitative with a case study design through interviews and observations. The results show that teachers are still in the early stages of adaptation due to limited understanding of the IDP, difficulties in developing formative assessments, and a lack of training, despite their high commitment to learning and collaboration. School facilities such as smart boards, projectors, visual media, and KOMBEL rooms support the implementation of the IDP, although some facilities are limited. In conclusion, teacher readiness has a direct impact on the effectiveness of RPM, so training, mentoring, and collaboration need to be continuously improved.